Prevalence of Postoperative Infection after Tooth Extraction: A Retrospective Study - Elaine Kueh Yue Yi; Annabelle Lai Siew Ying; Mandakini Mohan; Rohit Kunnath Menon (International Journal of Dentistry)
The aim of the study was to identify the postoperative infection rates after tooth extraction in a university dental clinic and to identify the factors associated with an increased risk for postoperative infection. A retrospective study of case records of patients who underwent tooth extractions at the International Medical University’s Oral Health Centre (IMU-OHC) over a span of 6 years was conducted. Data on demography, patient-related factors, and treatment-related factors were extracted from the case records. A binary logistic regression analysis was performed to assess the odds ratio of a patient having a postoperative infection or not, comparing it with each variable. A total of 1821 extractions, including simple and complex extractions, were performed over 6 years. Only 25 (1.4%) of the cases were reported to have a postoperative infection. The complexity of the extraction was the only variable that significantly affected the occurrence of postoperative infection after extraction; more complex extractions were reported with higher rates of infection (binary logistic regression, OR = 2.03, p = 0.004). None of the other factors, including antibiotic prescription, had a significant influence on the occurrence of postoperative infection. The prevalence of postoperative infection after dental extractions was low in IMU-OHC, and prescribing antibiotics had no added advantage in the prevention of postoperative infection.